Gejala Produktivitas Rendah dan Pertanian Degeneratif - Evizal, Rusdi; Prasmatiwi, Fembriarti Erry (JURNAL AGROTROPIKA, 2022)
Agronomy examines complex agricultural production concepts such as Sustainable Agriculture, Good Agricultural Practices, Regenerative Agriculture into the best practical technologies that farmers can apply. Important agronomic variables in agricultural cultivation include production and productivity. Plant productivity is influenced by many interacting factors. This paper aims to examine the symptoms of decreased productivity and symptoms of degenerative agriculture. The decline in production and productivity that continues in the long term indicates a degenerative agro-ecosystem. Degenerative agriculture is an agricultural practice that causes productivity to continue to decline as a result of a decrease in the carrying capacity of agro-ecosystems, including soil, plants and other flora, fauna, microbes, climate and society. The decrease in the carrying capacity of the soil is shown, among others, by land degradation, a decrease in soil organism diversity and activity, declining of organic matter content and the availability of nutrients in the soil due to nutrient depletion transported by harvest, erosion and inappropriate cultivation practices. In addition, it will discuss the factors driving the degenerative agroecosystem that interact with each other. These factors include land degradation, decreased biodiversity, continuous planting of varieties and species of plants, use of chemical inputs, pest and disease attacks, and climate change. Mitigating these factors means choosing a path to regenerative agriculture. Key words : Agroecosystem, biodiversity, degenerative, sustainable, regenerative, productivity